Social theory and education research - Murphy, Mark (SAGE, 2013)
Includes bibliographical references; Includes 4 volumes. Volume 1: Inequality, Inclusion and Education -- Volume 2: Identities: notions of educational selves and subjectivities -- Volume 3: Teaching and learning: curricular and pedagogical practice -- Volume 4: Governance and management: performativity, audit cultures and accountability